2020
DOI: 10.3348/kjr.2020.0067
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Coated Balloon versus Plain Balloon Angioplasty for Dysfunctional Autogenous Radiocephalic Arteriovenous Fistulas: A Prospective Randomized Controlled Trial

Abstract: Objective To report the mid-term results of a single-center randomized controlled trial comparing drug-coated balloon angioplasty (DBA) and plain balloon angioplasty (PBA) for the treatment of dysfunctional radiocephalic arteriovenous fistulas (RCAVFs). Materials and Methods In this prospective study, 39 patients (mean age, 62.2 years; 21 males, 18 females) with RCAVFs failing due to juxta-anastomotic stenosis were randomly assigned to undergo either both DBA and PBA (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…15,16 Since then, a number of small studies have included AVFs only, and have excluded patients with arteriovenous grafts (AVGs), intravascular stents or a central stenosis. [17][18][19][20][21] These studies gave conflicting results, and a small study in those with a central venous stenosis suggested benefit. 22 Four larger studies, each with over 100 subjects, have been published.…”
Section: Fundingmentioning
confidence: 99%
“…15,16 Since then, a number of small studies have included AVFs only, and have excluded patients with arteriovenous grafts (AVGs), intravascular stents or a central stenosis. [17][18][19][20][21] These studies gave conflicting results, and a small study in those with a central venous stenosis suggested benefit. 22 Four larger studies, each with over 100 subjects, have been published.…”
Section: Fundingmentioning
confidence: 99%
“…AVF with native vein was the most common type of access; only 128 lesions used AVG. Although one trial included central vein lesions exclusively, 24 in nine trials, 14,15,23,25,27,30,34,35,38 stenoses of the central vein were excluded (Supplementary Table 3). The mean age of the fistula included in the majority of the trials was > 2 years (Table 2).…”
Section: Trial Level Characteristics Of Interventions and Populationsmentioning
confidence: 99%
“…In four trials, DCB angioplasty was performed without pre-dilation of the stenotic lesion, 23,24,26,29 whereas DCBs were used after vessel preparation using high pressure uncoated balloons in 11 trials. 14,15,21,22,24,27,28,30,34,37,38 Of these, six trials 14,15,21,28,30,37 had patients enrolled and randomised to either the DCB or PB groups when successful pre-dilation was achieved.…”
Section: Procedural Characteristics Of the Included Randomised Controlled Trialsmentioning
confidence: 99%
“…The search strategy retrieved 503 studies; after de-duplication and screening, 11 RCTs [16,17,[41][42][43][44][45][46][47][48] comprising 1,243 patients were eligible and included in the meta-analysis [ Figure 1]. One RCT was excluded as no curve was provided for graphical reconstruction to retrieve patient-level patency information [49].…”
Section: Study Selectionmentioning
confidence: 99%
“…However, findings are mixed in the setting of hemodialysis access – some meta-analyses significantly favoured DCB over PTA [12, 13], while others reported no significant benefit [14, 15]. Not long ago, two new randomized controlled trials (RCTs) on this subject were published [16, 17]; this article aims to re-evaluate the field with these new inclusions. To our knowledge, this is first meta-analysis which includes these 2 new RCTs.…”
Section: Introductionmentioning
confidence: 99%